Designing a Paulinity-based character education curriculum aligned with Indonesia’s Merdeka Curriculum - Charles Thomana; Haryono Haryono; Yuli Utanto (Universitas Negeri Semarang, 2025)
This study examines the development of a character education curriculum at Yayasan Paulus Makassar, grounded in the core Paulinity values: Excellence (Unggul), Creativity (Kreatif), Love (Kasih), and Mission (Misioner). Using a research and development approach, it follows Hilda Taba’s model: diagnosis of needs, formulation of objectives, selection of content, selection of learning experiences, organization of learning experiences, and evaluation. Data were collected through observations and in-depth interviews with teachers, students, and members of the curriculum team. The study's results identified that the main basis of curriculum development is the Catholic Church's universal values and the intention to develop students’ characters in line with the Merdeka curriculum policy. Moreover, the voices of the members of the educational community become the primary consideration in curriculum development. This study offers insight into curriculum design processes and emphasizes the importance of Indonesia’s national curriculum in addressing character development alongside scientific challenges.